MiR-223 within neutrophil axis promotes Th17 expansion by PI3K-AKT pathway in systemic lupus erythematosus - Chengzhong Zhang; Yan Lu (Arthritis Research & Therapy)
Abstract Introduction Further investigation is required to determine the etiology of systemic lupus erythematosus (SLE). The aim of this study is to assess the presence of miR-223 within neutrophils in SLE and investigate its impact on the expansion of Th17 cells. Methods Experiments were performed in MRL/lpr mice, which were divided into control and miR-223 knockdown (miR-223-) group. We assessed miR-223 expression within neutrophils and Th17 expansion in MRL/lpr mice and patients with SLE using RT-PCR, luciferase reporter assay, Elisa, flow cytometry analysis. Signaling pathway, RT-PCR and western blot were conducted to elucidate the mechanism by which miR-223 within neutrophils expands Th17. Results We initially identified miR-223 as a pivotal factor in the pathogenesis of SLE in both MRL/lpr mice and SLE patients. Subsequently, knockdown of miR-223 led to a significant reduction in Th17 expansion in MRL/lpr mice. Moreover, inhibition of miR-223 effectively attenuated the recruitment and activation of neutrophils in SLE. Furthermore, we found rb6-8c5 treatment alleviated lupus symptoms of MRL/lpr mice and reduce the level of Th17. Finally, we elucidated that neutrophils potentiate the induction of Th17 through the activation of thePI3K-AKT pathway mediated by miR-223 during SLE-associated Th17 expansion. Conclusion MiR-223 within neutrophil axis contributes to Th17 expansion by PI3K-AKT pathway in SLE, and miR-223 could be a therapeutic target of SLE.